2019
DOI: 10.1111/oik.06586
|View full text |Cite
|
Sign up to set email alerts
|

Coping with multiple enemies: pairwise interactions do not predict evolutionary change in complex multitrophic communities

Abstract: Predicting the ecological and evolutionary trajectories of populations in multispecies communities is one of the fundamental challenges in ecology. Many of these predictions are made by scaling patterns observed from pairwise interactions. Here, we show that the coupling of ecological and evolutionary outcomes is likely to be weaker in increasingly complex communities due to greater chance of life‐history trait correlations. Using model microbial communities comprising a focal bacterial species, Bacillus subti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 87 publications
0
21
0
Order By: Relevance
“…For example, although, the taxon richness used here is large compared to most microbial competition studies (Bohannan and Lenski 2000a,b;Jiang and Adams Krumins 2006), our experimental communities were considerably less diverse than natural communities with respect to both bacterial prey taxa and predator species. It has been shown that more simple interactions cannot accurately predict the behaviour of complex communities (McClean et al, 2018). Moreover, our setup did not enable us to separate inter from intraspecific competition.…”
Section: Discussionmentioning
confidence: 92%
“…For example, although, the taxon richness used here is large compared to most microbial competition studies (Bohannan and Lenski 2000a,b;Jiang and Adams Krumins 2006), our experimental communities were considerably less diverse than natural communities with respect to both bacterial prey taxa and predator species. It has been shown that more simple interactions cannot accurately predict the behaviour of complex communities (McClean et al, 2018). Moreover, our setup did not enable us to separate inter from intraspecific competition.…”
Section: Discussionmentioning
confidence: 92%
“…Given the increasing popularity of laboratory evolution as a tool and the fact that natural communities often consist of a large number of interacting species, surprisingly few studies have extended the above approaches to communities of more than two species (but note [58], as well as an increasing body of work that asks how focal species evolve in the presence of a community [59][60][61][62]). One important exception is a study in which five species from a beech tree hole were cocultured in the laboratory for approximately 70 generations [63].…”
Section: Evolution Of Microbial Communities: Empirical Approachesmentioning
confidence: 99%
“…Finally, real communities consist of more than two species (or multiple strains of the same species, which should have similar consequences as long as these strains have sufficiently different growth characteristics and are unlikely to share the same cooperative gene (so that we can safely ignore kin selection [88,113])). This may spatially isolate interacting species [128,129], exert opposing selection pressures on a focal species [62] and result in higher-order interactions [24,130]. Predicting the joint effect of such forces is not straightforward.…”
Section: Conceptual and Computational Models For The Evolution Of Micmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the increasing popularity of laboratory evolution as a tool and the fact that natural 170 communities often consist of a large number of interacting species, surprisingly few studies 171 have extended the above approaches to communities of more than two species (but note Refs. 172 [56,57]). One important exception is a study in which five species from a beech tree hole 173 were cocultured in the lab for ~70 generations [58].…”
mentioning
confidence: 99%